2007
DOI: 10.1016/j.jpain.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity and Health-Related Quality of Life in Children With Chronic Pain

Abstract: Anxiety sensitivity (AS), or the fear of anxiety sensations has been shown to independently predict poorer health-related quality of life (HRQOL) in adults with chronic pain. Specifically, AS was found to contribute to decrements in psychological well-being and social functioning but not to decrements in physical functioning. Existing studies have not examined the relationship between AS and HRQOL in children with chronic pain. The present study used multivariate regression analysis to test the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 33 publications
4
31
0
3
Order By: Relevance
“…We observed that a high level of satisfaction with pain-related QOL was significantly associated with a decreased risk of anxiety. Although several studies 53,54 have explored pain and anxiety in adolescents, extremely few studies have focused on pain-related QOL. A study reported that higher anxiety sensitivity correlates with a higher fear of pain, which is associated with increased pain disability 55 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that a high level of satisfaction with pain-related QOL was significantly associated with a decreased risk of anxiety. Although several studies 53,54 have explored pain and anxiety in adolescents, extremely few studies have focused on pain-related QOL. A study reported that higher anxiety sensitivity correlates with a higher fear of pain, which is associated with increased pain disability 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the literature notes that chronic pain in children and adolescents causes school truancy, inability take part in physical activities, sleep disturbances and problems relating to people in the same age group (7,9,27) , these aspects were not identified in this study. Analysis of the accounts showed that children and adolescents kept a social support network through their school friends, neighbors and family members, who helped them have a life that is closer to normality.…”
Section: Discussionmentioning
confidence: 90%
“…Many children and adolescents with chronic diseases and/or in the end-of-life phase live with pain daily, in addition to other signs and symptoms, such as: fatigue, dyspnea, anorexia, nausea, vomiting, insomnia, anxiety, despair, frustration and impotence when managing daily situations (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety also plays a complex role in moderating the relationship between pain and function. Tsao et al (2007) studied anxiety sensitivity, or the fear of anxiety sensations, in 87 children aged 10-18 presenting at a US chronic pain clinic. Anxiety sensitivity was found to be linked with academic and/or social limitations, where those limitations arose from emotional rather than physical difficulties.…”
Section: The Impact Of Chronic Pain On Children and Their Familiesmentioning
confidence: 99%